Pengaruh Kepercayaan, Kualitas Produk, Dan Promosi Terhadap Keputusan Pembelian Online Shop Shopee (Study Kasus Komunitas Remaja Desa Kauman Kabupaten Jombang) - Mohammad Arif Firmansyah; Nur Hidayati; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the influence of trust, product quality and promotion on shopee online shop purchase decisions. The type of research is Explanatory Research using quantitative methods. The population in this study is the adolescent community of Kauman Jombang village. While the sample used in this study was to use a saturated sample where all populations were made into samples totaling 55 responses. The data used is primary data using questionnaires. The data analysis method used is an instrument test consisting of validity and reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests, multiple linear regression analysis, hypothesis tests consisting of simultaneous tests, partial tests and coefficients of determination. From the results of the study, it can be seen that simultaneously the results are obtained that trust, product quality, and promotions have a significant effect on shopee online shop purchase decisions. Partial results were obtained that trust has a significant effect on purchasing decisions, product quality affects purchasing decisions, promotions affect purchasing decisions Keywords: trust, product quality, promotion, purchase decision